2018
DOI: 10.31138/mjr.29.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Cross-sectional Study of Patients with Rheumatoid Arthritis in Greece: Results from a cohort of 2.491 patients

Abstract: Aim of the study:To evaluate the current disease characteristics, treatment and comorbidities of rheumatoid arthritis (RA) in Greece. Methods: Multicenter, cross-sectional study with a 9-month recruitment period between 2015 and 2016. Demographics, disease characteristics, treatment and comorbidities were collected via a web-based platform. Results: 2.491 RA patients were recruited: 96% from tertiary referral centers, 79% were females with a mean age of 63.1 years and disease duration of 9.9 years. Fifty-two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…In our recent multi-centre RA study 43 , the rate of pneumococcal and last year’s influenza vaccination was 36% and 32%, respectively indicating a significant deficit of preventive strategies and abundant space for interventions, as also shown in other recent studies. 62 Any concerns for disease flares after vaccination are unsubstantiated and should not prevent rheumatologists from vaccine prescription, since several studies have not showed such correlation.…”
Section: Opportunistic Infectionssupporting
confidence: 79%
See 1 more Smart Citation
“…In our recent multi-centre RA study 43 , the rate of pneumococcal and last year’s influenza vaccination was 36% and 32%, respectively indicating a significant deficit of preventive strategies and abundant space for interventions, as also shown in other recent studies. 62 Any concerns for disease flares after vaccination are unsubstantiated and should not prevent rheumatologists from vaccine prescription, since several studies have not showed such correlation.…”
Section: Opportunistic Infectionssupporting
confidence: 79%
“… 42 Recently, a similar LTBI prevalence (13–15%) has been found among 2491 Greek RA patients. 43 In the general population, IGRAs are recommended over TST for LTBI screening, given their higher specificity and ease of use. 44 However, for RA patients starting b- or ts-DMARDs, TST, IGRA or a dual screening strategy have been proposed ( Table 2 ).…”
Section: Opportunistic Infectionsmentioning
confidence: 99%
“…Patients with SSc were recruited consecutively between 2016 and 2017 and were matched 1:1 for age and gender with RA patients, all meeting the 1980 American College of Rheumatology (ACR) criteria [ 7 ] and the 1987 ACR criteria [ 8 ], respectively. RA patients were derived from the working cohort of an ongoing, multicenter prospective RA study involving 2491 patients (from the RA Study Group of the Greek Rheumatology Society) [ 9 ]. Ethical approval was provided by the local institutional boards of participating centers and informed consent was provided by all patients before their inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…11 – 13 The Greek scientific community has created databases with publications that describe the real-world treatment of patients within this framework, 14 – 18 including the achievement of different levels of disease activity in patients with RA. 16 …”
Section: Introductionmentioning
confidence: 99%